A Novel Approach Integrating Hierarchical Clustering and Weighted Combination for Association Study of Multiple Phenotypes and a Genetic Variant - Fu, Liwan; Wang, Yuquan; Li, Tingting; Hu, Yue-Qing (Frontiers in Genetics, 2021)
As a pivotal research tool, genome-wide association study has successfully identified numerous genetic variants underlying distinct diseases. However, these identified genetic variants only explain a small proportion of the phenotypic variation for certain diseases, suggesting that there are still more genetic signals to be detected. One of the reasons may be that one-phenotype one-variant association study is not so efficient in detecting variants of weak effects. Nowadays, it is increasingly worth noting that joint analysis of multiple phenotypes may boost the statistical power to detect pathogenic variants with weak genetic effects on complex diseases, providing more clues for their underlying biology mechanisms. So a Weighted phenotypic Combination approach following Hierarchical Clustering based on correlation coefficients between two sets of phenotypes (WCHC) is proposed for simultaneously analyzing multiple phenotypes in association studies. A series of simulations are conducted and the results show that WCHC is either the most powerful method or comparable to the most powerful competitor in most of the simulation scenarios. Additionally, we evaluated the performance of WCHC in its application to the obesity-related phenotypes from Atherosclerosis Risk in Communities and several associated variants are reported.